Motivation and job satisfaction - Idris, Hassan Abubakar; Quddus, S M Abdul (IIUM Press, International Islamic University Malaysia, 2017)
The study seeks to examine the level of job satisfaction among academic staff of Bauchi State University Gadau (BASUG), Nigeria. This Study uses motivator and hygiene factors as independent variables, whereas job satisfaction/motivation as a dependent variable is based on the theoretical framework of ‘two factor theory’ of Fredrick Herzberg (1959). This study employs 40 close-ended and 3 open-ended questions adapted and adopted from the Minnesota Satisfaction Questionnaire (MSQ) and interviews were also conducted to compliment the result of the survey questions in measuring the level of job satisfaction among 148 academic staff of BASUG that had participated in the study. Accordingly, descriptive and inferential statistics were used in testing the data collected. The findings reveal that there is positive and significant relationship between motivator factors and job satisfaction where ‘advancement’ is the strongest factor, followed by ‘responsibility’, ‘work itself’, ‘achievement’ and lastly ‘recognition’.